Distribution and sources of organic carbon, nitrogen and their isotopes in surface sediments from the largest mariculture zone of the eastern Guangdong coast, South China. Issue 1 (15th July 2017) - Gu, Yang-Guang; Ouyang, Jun; Ning, Jia-Jia; Wang, Zeng-Huan
Abstract: China is the world's largest mariculture producer. However, there is limited detailed information on organic matter distribution generated by mariculture in China. This study assessed the total organic carbon (TOC), total nitrogen (TN), and isotopic composition (δ 13 C and δ 15 N) in surface sediments from Zhelin Bay in South China. TOC, TN, δ 13 C and δ 15 N ranged from 0.46–1.23%, 0.08–0.20%, − 22.07 to − 21.13‰ and 5.28–7.14‰, respectively, and followed similar spatial patterns. The C/N ratio coupled with isotopic composition (δ 13 C and δ 15 N), indicates that the TOC originated from both terrestrial and marine sources. In general, surface sediments of Zhelin Bay were dominated by marine derived organic carbon; this form of carbon was separately calculated based on δ 13 C-based two end-member mixing and C/N ratio models. Graphical abstract: Highlights: Total organic carbon (TOC), total nitrogen (TN), δ 13 C and δ 15 N in sediments of Zhelin Bay were measured. The spatial patterns of TOC TN, δ 13 C and δ 15 N were similar. Surface sediments were dominated by marine derived organic carbon.